2010
DOI: 10.1134/s1068162010060117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of secasterol and 24-episecasterol and their toxicity for MCF-7 cells

Abstract: A convergent synthesis of biosynthetic precursors of brassinosteroids - secasterol and 24-episecasterol with Δ²-bond in cycle A is described. The key stages in the construction of the side chain of these compounds were Julia olefination of steroid 22-aldehyde followed by asymmetric Sharpless dihydroxylation of the intermediate Δ²²-olefin. Toxicity of synthesized compounds against breast carcinoma MCF-7 cells was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Similar results were obtained for derivatives with a campestane, ergostane [117] and cholestane [118] carbon skeletons. Thus, (22R,23R)-diols 13 and 14 were more cytotoxic (IC 50 1.6-1.8 lM)…”
Section: Anticancer Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained for derivatives with a campestane, ergostane [117] and cholestane [118] carbon skeletons. Thus, (22R,23R)-diols 13 and 14 were more cytotoxic (IC 50 1.6-1.8 lM)…”
Section: Anticancer Effectssupporting
confidence: 88%
“…for MCF-7 cells in comparison with the corresponding (22S,23S)-isomers (IC 50 >49 lM) [117]. Low-polar diols 15 and 16 were found to be the most efficient among tested (22R,23R)-22,23-dihydroxycholestanes including 28-norcastasterone and 28-norbrassinolide [118].…”
Section: Anticancer Effectsmentioning
confidence: 97%
“…For introduction of Δ 2 bond in A ring, we used the reaction of isomerization of 6 oxo 3α,5 cyclo 5α steroids to 6 oxo Δ 2 5α steroids by refluxing with pyridinium bromide in dimethylacetamide [21]. Pre viously, using 28C steroids as an example, we showed that the 22,23 diol group is not sufficiently stable under the conditions of this reaction [14]. The best results with regard to total yield of the target Δ 2 deriv atives were obtained during the rearrangement of the corresponding protected derivatives.…”
Section: Resultsmentioning
confidence: 98%
“…Their ability to suppress growth and induce the death of cancer cells in animals is even more interesting [9,10]. It should be noted that not only BRs with the full set of functional groups are active, but also their analogues or biosynthetic precur sors, in particular, these containing the low polar groups in the cyclic moiety [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, non-deuterated 24-episecasterol was prepared and found to be cytotoxic in human breast carcinoma MCF-7 cells. 18 The two electrophilic reactions, epoxidation and dihydroxylation of the olefin 10, gave epoxide 11 and 24-epicastasterone 12, correspondingly. Compound 11 is a 2a,3a-epimer of natural brassinosteroid 24-episecasterone found in Lychnis viscaria seeds.…”
mentioning
confidence: 99%